Traditional and new knowledge and practices in the food system transition - Salavisa, I.; Ferreiro, M. de F. (Proceedings of the European Conference on Knowledge Management, ECKM 2019, 2019)
The aim of this paper is to study how distinct generations of knowledge and technology are used for implementing innovative and sustainable production and commercialization practices in the food system. Transition towards sustainability encompasses structural changes in technological, organizational and social domains. In the case of the food systems, notably agriculture, the shift is from a 'productivist' to a 'post-productivist' paradigm. This change takes place via the scaling up of experimental and isolated cases (niches), through the creation of organic farms and the transformation of conventional ones. The post-productivist mode of agricultural production relies on principles such as high quality products, certified practices, environmental conservation, local embeddedness and alternative forms of commercialization. Conversely, economic efficiency prevails in the dominant 'productivist' mode. On the one hand, new technologies, namely in information and communication, play an important role in the shift to sustainable businesses in the food system. The Internet has become extensively used in the commercialization processes, while biotechnology advances (developed in universities, and public and privately owned laboratories) are increasingly incorporated in farming. On the other hand, traditional sources of innovation consist of the re-usage and adaptation of 'old' knowledge, practices and techniques. Local production and short supply chains, which allow the creation of innovative businesses, are examples of this phenomenon. These cases exemplify how traditional activities can absorb/generate innovation, at technological and organizational levels, and adapt to the new knowledge-based era. The research presented in the paper has been conducted in a project on Spatial Planning for Change (SPLACH). The analysis focus on the food system transition in a specific territory, the Lisbon Metropolitan Area. The paper addresses the combination of different technologies in organic food production initiatives in the Lisbon Metropolitan Area (LMA). Primary data were collected through in-depth interviews with key actors, namely entrepreneurs or leaders of the initiatives.